Efficient Energy Usage Model for WSN-IoT Environments - Thangarasu, G. (Institute of Electrical and Electronics Engineers Inc., 2020)
Nowadays, the usage of Wireless Sensor Networks (WSN) with Internet of Things (IoT) is increasing in many commercial and industrial applications to perform various tasks inexpensively. Internet of Things (IoT) is the expansion of smart objects and Wireless Sensor Networks by interfacing distributed and identifiable communication devices. The accessibility of imbalanced resources and heterogeneous IoT communication leads to vitality utilization imperatives. This study proposed an improved Chaotic Whale Optimization model to improve the utilization of vitality. The proposed system result shows better vitality effectiveness in coordinates WSN-IoT environment. Â© 2020 IEEE.